Development and Validation of a Stability-Indicating Reversed-Phase High-Performance Liquid Chromatography (RP-HPLC) Method for Identification, Assay, and Estimation of Related Substances of Ivermectin Drug Substance. (21st July 2021) - Wimalasinghe, Rasangi M; Zhao, Daoli; Wang, Lin; Rustum, Abu
Abstract: Background: Ivermectin is a potent semi-synthetic antiparasitic drug used in veterinary medicine. It is widely used for the treatment of parasites. Objective: This study aimed to develop a stability-indicating reversed-phase HPLC (RP-HPLC) method for assay and identification of ivermectin including identification and estimation of its related substances in bulk drug substance batches of ivermectin. Method: Ivermectin and its related substances were separated on an Ascentis Express C18 column (100 mm × 4.6 mm id, 2.7 µm particle size) maintained at 45°C (column temperature) on an HPLC system with gradient elution. The mobile phase was composed of water − acetonitrile (ACN; 50 + 50, v/v) as mobile phase A, and isopropanol − ACN (15 + 85, v/v) as mobile phase B. Analytes were detected with a detection wavelength of 252 nm and quantitated against an external reference standard of ivermectin with a quantitation limit of 0.1% of the target (analytical) concentration. Results: The HPLC method was able to separate all analytes of interest by gradient elution within 25 min. The method was validated according to the guidelines described in the International Conference on Harmonization guideline Q2(R1). Conclusions: The HPLC method for assay of ivermectin and estimation of its related substances was successfully developed, validated, and demonstrated to be accurate, robust, specific, and stability indicating. Highlights: The performance of the HPLC method is significantly faster and possesses a higher degree of selectivity. Implementation of this method for routine analysis in QC laboratories would save significant time, resources and solvents.